2022
DOI: 10.1152/ajpregu.00321.2021
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of high-altitude exposure on markers of oxidative stress, antioxidant capacity, and iron profiles

Abstract: High altitude (HA) exposure may stimulate significant physiological and molecular changes, resulting in HA-related illnesses. HA may impact oxidative stress, antioxidant capacity and iron homeostasis, yet it is unclear how both repeated exposure and HA acclimatization may modulate such effects. Therefore, we assessed the effects of weeklong repeated daily HA exposure (2,900m to 5,050m) in altitude-naïve individuals (n=21, 13 females, mean ± SD, 25.3 ± 3.7 years) to mirror the working schedule of HA workers (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…(Rusko et al, 2004;Wilber, 2007;Gore et al, 2013). The U-shaped curve and upper limit of the reasonable dosage are novel findings that may arise from the adverse effects exerted by prolonged chronic hypoxia such as disrupted sleep quality (Kinsman et al, 2005;Sargent et al, 2013), oxidative disorders or pulmonary edema (Gaur et al, 2021;Rytz et al, 2022), accumulated fatigue (Bergeron et al, 2012;Koehle et al, 2014), etc. Moreover, the effect of training site altitude and type of hypoxic residential environment on the efficacy of HL was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Rusko et al, 2004;Wilber, 2007;Gore et al, 2013). The U-shaped curve and upper limit of the reasonable dosage are novel findings that may arise from the adverse effects exerted by prolonged chronic hypoxia such as disrupted sleep quality (Kinsman et al, 2005;Sargent et al, 2013), oxidative disorders or pulmonary edema (Gaur et al, 2021;Rytz et al, 2022), accumulated fatigue (Bergeron et al, 2012;Koehle et al, 2014), etc. Moreover, the effect of training site altitude and type of hypoxic residential environment on the efficacy of HL was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite variations in selected indicators, the effective hypoxic dosage in previous studies aligns closely with the reasonable range explored in this study ( Rusko et al, 2004 ; Wilber, 2007 ; Gore et al, 2013 ). The U-shaped curve and upper limit of the reasonable dosage are novel findings that may arise from the adverse effects exerted by prolonged chronic hypoxia such as disrupted sleep quality ( Kinsman et al, 2005 ; Sargent et al, 2013 ), oxidative disorders or pulmonary edema ( Gaur et al, 2021 ; Rytz et al, 2022 ), accumulated fatigue ( Bergeron et al, 2012 ; Koehle et al, 2014 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Our present findings would correlate with athletes that utilize altitude training to increase their exercise capacity; where being in a hypoxic environment would improve their performance at sea level or acclimatize to sports events at HA. A recent study reported that repeated and continuous exposure to HA might significantly alter oxidative stress and antioxidant capacity among HA visitors [63]. Another review highlighting the effect on telomere length and telomerase activity due to physical exercise concluded that regular aerobic activity, of moderate to vigorous intensity, preserves telomere length among athletes [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is sensitive to pathophysiological changes such as reduced antioxidant capacity, and oxidative damage can impede prefrontal-dependent memory function by reducing the production of new neurons ( Huang et al, 2015 ). A previous study showed that the levels of protein oxidation and catalase activity increased, and serum iron, serum ferritin, and transferrin saturation levels decreased with high-altitude exposure, indicating that the high-altitude environment may affect antioxidant capacity and iron homeostasis ( Rytz et al, 2022 ). The level of antioxidant capacity is closely related to the influence of high altitude, which was also found by Zhang et al (2015) during research on the effect of hyperbaric oxygen preconditioning in plain migrant plateau personnel.…”
Section: Discussionmentioning
confidence: 99%